Calles vs. Calles. El "jefe máximo" con la República, el exiliado con Franco. Contradicciones de la élite revolucionaria mexicana - Meyer, Lorenzo (El Colegio de México, A.C., 2009)
Flexibility, or rather ideological contradictions are among the characteristics of the Mexican Revolution. Historical perspective could lead to the conclusion that the absence of orthodoxy was not necessarily negative in relation to the regime that arose from the revolution. General Plutarco Elías Calles illustrates this trend. As the Revolution's “Jefe Máximo” [commander in chief] he supported the Spanish Republic openly and enthusiastically; the purchase of vessels from Spanish shipbuilders affected by the Great Depression proves this point. However, in stark contradiction to his earlier position, once in exile General Calles participated in a conspiracy seeking financial aid from the Government that overthrew the Spanish Republic. In 1940 he tried to organize  a movement against President Lázaro Cárdenas' regime in order to put an end to his reform programme.